Towards a model of organizational citizenship behaviour where it matters the most : civil society workplaces : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Psychology at Massey University (Albany Campus), New Zealand - Langdon, Steven James (Massey University, 2022)
Organizational citizenship behaviour is argued to be particularly important to civil society organizations, especially during a pandemic. However, organizational citizenship behaviour needs further theoretically driven research in the civil society sector, which is the overarching aim of this thesis. This thesis identifies two competing measurement models of organizational citizenship behaviour, and a corresponding need to explore its correlates, positioned as proximal correlates (burnout and engagement) and related job attitudes. This thesis recruited N = 442 employees from 217 civil society organizations in New Zealand. Confirmatory factor analysis, interclass correlation coefficients, and within-group agreement indices tested two competing measurement models of organizational citizenship behaviour. These analyses revealed that employees of civil society organizations tended to perform citizenship behaviour in accordance with one of the models: Organ’s (1988) five-factor organizational citizenship behaviour, independent of their organization. Using the data collected from New Zealand’s civil society sector, two-stage structural equation modelling (SEM) was used to develop and test two models of correlates to organizational citizenship behaviour. The results of this analysis suggest that perceived time demands linked positively to burnout, which in turn had a weak positive link to organizational citizenship behaviour. In addition, there was a positive link between citizenship motivation and engagement, which then had a positive relationship with Organ’s (1988) five sub-facet based organizational citizenship behaviour. As a comparative analysis, one-stage meta-analytic structural equation modelling was used to develop and test simplified comparison models of the correlates to organizational citizenship behaviour in the wider literature, that is, excluding civil society. N = 34 independent samples were included in the meta-analysis. The meta-analytic results suggested that negative job attitudes had a positive relationship with burnout, but burnout had no relationship with organizational citizenship behaviour. However, positive job attitudes had a positive relationship with engagement, which in turn had a positive relationship with organizational citizenship behaviour in the wider organizational literature. The thesis revealed that there is a key difference between correlates to organizational citizenship behaviour in the wider literature, as tested in the meta-analysis, and in New Zealand’s civil society sector, as tested by structural equation modelling. The relationship between burnout and organizational citizenship behaviour differs across the for-profit and civil society sectors. Burnout was found to have a positive relationship with organizational citizenship behaviour in the civil society sector, but not in the meta-analytic test of the for-profit sector.
Copyrighted test questionnaires are re-used with permission.
Keywords: Organizational behavior; Mathematical models; Civil society; New Zealand; 520104 Industrial and organisational psychology (incl. human factors)